2001
DOI: 10.1126/science.1064171
|View full text |Cite
|
Sign up to set email alerts
|

Glacial-to-Holocene Redistribution of Carbonate Ion in the Deep Sea

Abstract: We have reconstructed the glacial-age distribution of carbonate ion concentration in the deep waters of the equatorial ocean on the basis of differences in weight between glacial and Holocene foraminifera shells picked from a series of cores spanning a range of water depth on the western Atlantic's Ceara Rise and the western Pacific's Ontong Java Plateau. The results suggest that unlike today's ocean, sizable vertical gradients in the carbonate ion concentration existed in the glacial-age deep ocean. In the eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
100
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(113 citation statements)
references
References 30 publications
11
100
0
2
Order By: Relevance
“…7), particularly given further uncertainties associated with the carbonate system such as coral reef building (Vecsei and Berger, 2004). A small change in saturation is consistent with estimates of carbonate ion concentration during the last glacial (Broecker and Clark, 2001;Anderson and Archer, 2002), which suggest changes in the distribution of water masses but little change in overall concentration. We also note that the additional flux of CO 2 from volcanoes is consistent with inferences that no one oceanic mechanism is capable of explaining the glacial/interglacial changes in atmospheric CO 2 (e.g.…”
Section: Ocean Carbonate Compensationsupporting
confidence: 61%
“…7), particularly given further uncertainties associated with the carbonate system such as coral reef building (Vecsei and Berger, 2004). A small change in saturation is consistent with estimates of carbonate ion concentration during the last glacial (Broecker and Clark, 2001;Anderson and Archer, 2002), which suggest changes in the distribution of water masses but little change in overall concentration. We also note that the additional flux of CO 2 from volcanoes is consistent with inferences that no one oceanic mechanism is capable of explaining the glacial/interglacial changes in atmospheric CO 2 (e.g.…”
Section: Ocean Carbonate Compensationsupporting
confidence: 61%
“…They subsequently used these calibrations to reconstruct paleo- [CO 3 = ] bw in the glacial oceans (e.g. Broecker and Clark, 2001b;Broecker et al, 2001). Rosenthal and Lohmann (2002) demonstrated that the pre-exponential constant, B, in the Mg/Ca temperature calibration equation (Eq.…”
Section: Effects Of Partial Dissolutionmentioning
confidence: 99%
“…Foraminiferal size-normalised weight (SNW) has variously been used as either a tracer of the carbonate saturation state of bottom waters (reflecting dissolution of carbonate shells after death, e.g. Lohmann, 1995;Broecker and Clark, 2001), or as a proxy for the surface ocean carbonate system (reflecting the environmental conditions experienced by foraminifera over the course of their lifetime, e.g. Barker and Elderfield, 2002;Bijma et al, 2002;Moy et al, 2009;Marshall et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Many early studies used sieve-based weight measurements, where SNW is calculated as the measured mass of pooled individuals within a set sieve-size fraction divided by the number of individual tests (e.g. Lohmann, 1995;Broecker and Clark, 2001). However, shell size can vary within a studied sieve range (Beer et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%